Path Analysis on the Biopsychosocial and Economic Determinants of Quality of Life in Patients with Type II Diabetes Mellitus: Evidence from Surakarta, Central Java - Rahsunji Intan Nurvitasari; Didik Gunawan Tamtomo; Yulia Lanti Retno Dewi (Masters Program in Public Health, 2020)
Background: Type 2 diabetes mellitus (DM) is a chronic disease that is increasing to an alarm